2017
DOI: 10.2147/ott.s131014
|View full text |Cite
|
Sign up to set email alerts
|

Association between <em>TP53</em> gene Arg72Pro polymorphism and Wilms&rsquo; tumor risk in a Chinese population

Abstract: Wilms’ tumor is one of the most prevalent pediatric malignancies, ranking fourth in childhood cancer worldwide. TP53 is a critical tumor suppressor gene, which encodes a 53 kDa protein, p53. The p53 functions to protect against cancer by regulating cell cycle and apoptosis and maintaining DNA integrity. TP53 gene is highly polymorphic. Several TP53 gene polymorphisms have been considered to be associated with cancer risk. Of them, a nonsynonymous polymorphism, Arg72Pro (rs1042522 C>G), has been most extensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The 145 cases in the study were individuals newly diagnosed with neuroblastoma from the Guangzhou Women and Children’s Medical Center 19, 20, 21, 22, 23, 35. All tumors were histopathologically confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The 145 cases in the study were individuals newly diagnosed with neuroblastoma from the Guangzhou Women and Children’s Medical Center 19, 20, 21, 22, 23, 35. All tumors were histopathologically confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Liu et al [39] revealed that the effect of TP53 rs1402522 polymorphism on Wilms tumor risk is very weak, which is consistent with our result. Another study conducted by Fu et al [40] also showed no significant association between TP53 rs1402522 polymorphism and Wilms tumor risk, and they found that CG/GG genotypes carriers significantly increased Wilms tumor risk in children younger than 18 months of age, compared with CC genotype carriers. Moreover, it is reported that TP53 rs1042522 may not confer susceptibility to cancers, such as neuroblastoma [41], retinoblastoma [42].…”
Section: Discussionmentioning
confidence: 92%
“…For the present study, 145 patients with newly diagnosed and histologically confirmed Wilms’ tumor were recruited from the Department of Pediatric Urology, Guangzhou Women and Children's Medical Center between March 2001 and June 2016, while 531 cancer-free children undergoing routine physical examinations in the same hospital were randomly selected as controls. All the subjects were genetically unrelated ethnic Han Chinese from South China [ 24 , 25 , 43 ]. The response rate was approximately 90% for Wilms’ tumor patients and 95% for cancer-free controls.…”
Section: Methodsmentioning
confidence: 99%
“…The Wilms’ tumor gene was the first identified suppressor of Wilms’ tumor development [ 19 ]. Thereafter, several susceptibility genes were found predispose individuals to Wilms’ tumor, such as FWT1 [ 20 ], FWT2 [ 21 ], BRCA2 [ 22 ], TP53 [ 23 , 24 ], BARD1 [ 25 ] and CTR9 [ 26 ]. The LIM domain only 1 ( LMO1 ) gene is located at 11p15, and encodes a cysteine-rich two-LIM-domain transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%